2011
DOI: 10.1002/aic.12696
|View full text |Cite
|
Sign up to set email alerts
|

Steam gasification of a cellulose surrogate over a fluidizable Ni/α‐alumina catalyst: A kinetic model

Abstract: Catalytic steam gasification of a cellulose surrogate using a fluidizable Ni/α‐alumina catalyst is presented. Experiments were carried out in the CREC fluidized riser simulator. On this basis, a reaction network and a kinetic model for biomass catalytic steam gasification were proposed. This kinetic model was developed using a sound reaction engineering approach where reaction rates for various species are the result of the algebraic addition of dominant reactions. The modeling procedure also included the deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…8 and compared with values obtained in previous studies by our research team (17,18), using glucose and 2-methoxy-4-methylphenol and 20% Ni/5% La 2 O 3 -γAl 2 O 3 and 2.5% Ni-αAl 2 O 3 catalysts. [2,19]. Regarding the magnitude of the activation energy for the water-gas shift, a value of 20.21 kJ/mol was estimated in the present study, which is within the range of the activation energies reported in the literature (17.5-26.6 kJ/mol) [20,21].…”
supporting
confidence: 86%
See 2 more Smart Citations
“…8 and compared with values obtained in previous studies by our research team (17,18), using glucose and 2-methoxy-4-methylphenol and 20% Ni/5% La 2 O 3 -γAl 2 O 3 and 2.5% Ni-αAl 2 O 3 catalysts. [2,19]. Regarding the magnitude of the activation energy for the water-gas shift, a value of 20.21 kJ/mol was estimated in the present study, which is within the range of the activation energies reported in the literature (17.5-26.6 kJ/mol) [20,21].…”
supporting
confidence: 86%
“…• SRM for steam methane reforming reaction with values larger than those reported by Mazumder et al [18] and significantly bigger than those from Salaices et al [19]. On the other hand, the activation energy value of 63.9 kJ/mol s obtained which is close to the range reported in the literature (70-141 kJ/mol) [21][22][23][24][25][26].…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Salaices et al were the first ones to overcome this dilemma by demonstrating the viability of establishing, as is demonstrated in the upcoming sections, kinetic models using a sound reaction engineering approach. Reaction rates for various species were expressed as the algebraic addition (“additive effect”) of the dominant reactions as follows: r i = normalν W G S , i r W G S , r normalν W G S , r + normalν S R , i r S R , r normalν S R , r + normalν D R M , i r D R , r normalν D R , r where r W G S , H 2 = k W G S ACS:no-reduce p C O p H 2 O 1 + 2 K C O 2 A …”
Section: Kinetic Studies Of Catalytic Steam Gasification Of Biomassmentioning
confidence: 99%
“…Although measuring the total molar flow rate has a faster response time than measuring the outlet gas composition, it only presents the total reaction conversion and is not able to predict the individual conversion of reactions involved in the gasification. Salaices et al [15,16] studied the kinetics of cellulose gasification in a batch fluidized bed reactor. They calculated the overall conversion by measuring the total pressure in the reactor and were able to sample at several times and determine the production rate of each individual gas.…”
Section: Introductionmentioning
confidence: 99%